Time to definitive care within major trauma networks in England. Issue 5 (9th July 2020) - Haslam, N R; Bouamra, O; Lawrence, T; Moran, C G; Lockey, D J
Abstract: Background: Significant mortality improvements have been reported following the implementation of English trauma networks. Timely transfer of seriously injured patients to definitive care is a key indicator of trauma network performance. This study evaluated timelines from emergency service (EMS) activation to definitive care between 2013 and 2016. Methods: An observational study was conducted on data collected from the UK national clinical audit of major trauma care of patients with an Injury Severity Score above 15. Outcomes included time from EMS activation to: arrival at a trauma unit (TU) or major trauma centre (MTC); to CT; to urgent surgery; and to death. Results: Secondary transfer was associated with increased time to urgent surgery (median 7·23 (i.q.r. 5·48–9·28) h versus 4·37 (3·00–6·57) h for direct transfer to MTC; P < 0·001) and an increased crude mortality rate (19·6 (95 per cent c.i. 16·9 to 22·3) versus 15·7 (14·7 to 16·7) per cent respectively). CT and urgent surgery were performed more quickly in MTCs than in TUs (2·00 (i.q.r. 1·55–2·73) versus 3·15 (2·17–4·63) h and 4·37 (3·00–6·57) versus 5·37 (3·50–7·65) h respectively; P < 0·001). Transfer time and time to CT increased between 2013 and 2016 ( P < 0·001). Transfer time, time to CT, and time to urgent surgery varied significantly between regional networks ( P < 0·001). Conclusion: Secondary transfer was associated with significantly delayed imaging, delayed surgery, and increased mortality. Key interventions were performed more quickly in MTCs than in TUs. Graphical Abstract: This article describes timelines from emergency service activation to urgent surgery for seriously injured patients in England following implementation of regional trauma networks in 2012. Analysis showed that seriously injured patients undergoing secondary transfer to definitive care had delayed imaging, delayed surgery and increased mortality. The findings suggest that direct transfer to a major trauma centre (MTC) (bypassing other hospitals where safe to do so) may result in seriously injured patients receiving surgery and other key interventions more quickly. TARN, Trauma and Audit Research Network; ISS, Injury Severity Score; TU, trauma unit. Poor results with secondary transfers